Changes in glacial meltwater alter algal communities in lakes of Scoresby Sund, Renland, East Greenland throughout the Holocene: abrupt reorganizations began 1000 years before present - Slemmons, Krista E.H.; Medford, Aaron; Hall, Brenda L.; Stone, Jeffery R.; McGowan, Suzanne; Lowell, Thomas; Kelly, Meredith; Saros, Jasmine E. (SAGE, 2017)
We investigated the response of lake algal communities to changes in glacial meltwater from the Renland Ice Cap (Greenland) through the Holocene to assess whether influxes always elicit consistent responses or novel responses. We measured sedimentary algal pigments in two proximal lakes, snow-fed Raven and glacier- and snow-fed Bunny Lake, and diatom community structure and turnover in Bunny Lake. Diatom data were not available in Raven Lake. We also modeled lake-level change in Bunny Lake to identify how glacial meltwater may have altered diatom habitat availability through time. Through a series of glacier advances and retreats over the Holocene, the algal response in Bunny Lake was relatively constant until approximately 1015 yr BP, after which there were major changes in sedimentary algal remains. Algal pigment concentrations sharply declined, and diatom species richness increased. Diatom community structure underwent three reorganizations. Until 1015 yr BP, assemblages were dominated by Pinnularia braunii and Aulacoseira pffaffiana. However, approximately 1015–480 yr BP, these species declined and Tabellaria flocculosa and Hannaea arcus became a significant component of the assemblage. Approximately 440 yr BP, A. pfaffiana increased along with species indicating elevated nitrogen. In contrast, the algal pigment records from nearby snow-fed Raven Lake showed different and minimal change through time. Our results suggest that changes in the magnitude and composition of meltwater in our two study lakes were unique over the last 1000 yr BP and elicited a non-linear threshold response absent during other periods of glacier advance and retreat. Deciphering the degree to which glaciers structure algal communities over time has strong implications for lakes as glaciers continue to recede.